Competition-Based Puzzle Media to Improve Science Learning Outcomes in the Story about My Region Material in Grade IV Elementary School - Putu Intan Sukma Mahayani; I Nyoman Jampel; Kadek Yudiana (Universitas Pendidikan Ganesha, 2025)
The low level of student learning achievement and the limited variety of innovative instructional media in the IPAS subject highlight the need for the development of media that can enhance student engagement and the quality of the learning process. This study aims to develop and evaluate the feasibility of a competition based puzzle medium in terms of its validity, practicality, and effectiveness for the topic Cerita tentang Daerahku. The study employs a Research and Development approach using the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The participants consisted of 20 fourth grade elementary school students. Data were collected through validation questionnaires completed by subject matter and media experts, practicality questionnaires completed by teachers and students, and learning outcome tests in the form of pretests and posttests. Data analysis used quantitative descriptive techniques to assess validity and practicality, and a paired-samples t-test to examine media effectiveness. The results showed average validity scores of 4.75 for the content aspect and 4.70 for the media aspect, both categorized as very valid. The practicality of the media reached 96% based on teacher responses and 89.80% based on student responses. The effectiveness test indicated an improvement in learning outcomes from a mean pretest score of 41.00 to a posttest score of 73.66, with t = 18.115 and p < 0.05. The implications of this study suggest that competition based puzzle media enrich IPAS learning through participatory approaches, the integration of physical and digital media, and the strengthening of twenty-first-century skills.